Play On Words on Nurhadi-Aldo Political Memes - Intan Rawit Sapanti (Komunikator, 2019)
Political satire in form of Nurhadi-Aldo meme arise ahead of Presidential Election 2019 was one of the society reaction towards the massive black or negative campaign happening nowadays. These fictitious couple emerge as a form of refreshment that could entertain the society through its humorous meme. This research aims to explore about the word play used in Nurhadi-Aldo meme. This research conducted in qualitative research using observation and noting data collection technique, and then the researcher used the descriptive method for the data analysis. The result of this research shows two language aspects used in this meme; phonological and semantic aspects. There are two strategies used in phonological aspects; using rime and sound repetition. There are 5 strategies used in semantic aspects; using proverbs, abbreviation, polysemi, metafora and syllogism.